Monophenyltin Derivatives of Some N-[o-Hydroxy Substituted (or H) Benzyl] Glydnes. - SlVADASAN, PRASANTHAN; CHANDRA, MADHIJP (Asian Journal of Chemistry, 2010)
Several monophenyltin derivatives of N-[o-hydroxy substituted (or H) benzyl] glycines have been prepared by the interaction of monophenyltin triisopropoxide with the latter in 1 : 1, 1 : 2 and 1 : 3 molar ratios in benzene medium. The various compounds thus prepared were obtained as coloured solids with some of them being hygroscopic. All these compounds were characterized by azeotrope and elemental analyses, as well as by IR and PMR spectral measurements.